Nepali Text to Speech Synthesis System using FreeTTS
This paper confers the tools and methodology used in developing a Nepali Text to Speech Synthesis System using FreeTTS and is entirely developed in Java and uses FreeTTS synthesize1: Vocalized form of human communication is Speech. Here the Nepali Language is Synthetized based on formant approach and the use of one of the popular generic frameworks FreeTTS that is available in public domain for the development of a TTS system. The Text To Speech Architecture has been developed putting more emphasis on the Natural Language Processing (NLP) component rather than Digital Signal Processing (DSP) component. Nepali language being mostly used language in Nepal and some parts of India and abroad, a text-to-speech (TTS